THE EPIDEMIOLOGICAL CHARACTERISTICS OF MEASLES IN VARNA REGION FOR 2005-2016 - Elyana P. Ivanova; Gabriela St. Tsankova; Tatina T. Todorova; Neli M. Ermenliev; Rumen P. Konstantinov; Yanka V. Draganova; Milena Petkova (Peytchinski Publishing, 2018)
Purpose: Measles is a highly contagious disease, and despite the presence of an effective and safe vaccine, it is still a leading cause of child mortality. During 2009-2010, the most serious European outbreak of measles occurred in Bulgaria and killed24 children. The severity of the recent epidemic outbreak prompts us to investigate the epidemiology of measles in Varna Region from 2005 to 2016. We also tried to assess the prevention measures analyzing the vaccine coverage during the post-outbreak period. Materials and methods: We performed a retrospective study (2005-2016) on the base of the epidemiological data for the measles incidence from the Regional Health Inspectorate - Varna. Results: During 2010 the incidence of measles in Varna Region reached 289.47 cases per 100000 inhabitants. The disease showed a typical winter-spring seasonality and affected people of all ages but the highest incidence was reported among children <1 year (4288.90 cases per 100000) and among the Roma ethnic group. The analysis of the number of performed immunizations during the period after the outbreak (2011-2015) showed a low immunization coverage (around and under 90%). Conclusions: The epidemiological analysis of the recent measles outbreak and its dimension in Varna Region showed alarming results: failure to vaccinate the required number of individuals led to the accumulation of a significant number of unvaccinated people and therefore to possible re-emergence of measles in the near future.